Short course of grass allergen peptides immunotherapy over 3 weeks reduces seasonal symptoms in allergic rhinoconjunctivitis with/without asthma: A randomized, multicenter, double‐blind, placebo‐controlled trial. Issue 9 (21st June 2018) - Mösges, R.; Bachert, C.; Panzner, P.; Calderon, M. A.; Haazen, L.; Pirotton, S.; Wathelet, N.; Durham, S. R.; Bonny, M.‐A.; Legon, T.; von Frenckell, R.; Pfaar, O.; et al.
Abstract: Background: Immunotherapy with peptide hydrolysates from Lolium perenne (LPP) is an alternative treatment for seasonal allergic rhinitis with or without asthma. The aim of this study was to assess the clinical efficacy and safety of a cumulative dose of 170 μg LPP administered subcutaneously over 3 weeks. Methods: In a randomized, double‐blind, placebo‐controlled trial, 554 adults with grass pollen rhinoconjunctivitis were randomized (1:2 ratio) to receive 8 subcutaneous injections of placebo or 170 μg LPP administered in increasing doses in 4 visits over 3 weeks. The primary outcome was the combined symptom and medication score (CSMS) measured over the peak pollen season. Reactivity to conjunctival provocation test (CPT) and quality of life (QOL) was assessed as secondary endpoints. Results: The mean reduction in CSMS in the LPP vs placebo group was −15.5% ( P = .041) during the peak period and −17.9% ( P = .029) over the entire pollen season. LPP‐treated group had a reduced reactivity to CPT ( P < .001) and, during the pollen season, a lower rhinoconjunctivitis QOL global score ( P = .005) compared with placebo group. Mostly mild and WAO grade 1 early systemic reaction (ESR) were observed ≤30 minutes in 10.5% of LPP‐treated patients, whereas 3 patients with a medical history of asthma (<1%) experienced a serious ESR that resolved with rescue medication. Conclusion: Lolium perenne pollen peptides administered over 3 weeks before the grass pollen season significantly reduced seasonal symptoms and was generally safe and well‐tolerated. Abstract : Short course of Lolium perenne immunotherapy over 3 weeks significantly reduced seasonal symptoms and the need of rescue medication intake. Lolium perenne immunotherapy was safe and well tolerated. Lolium perenne immunotherapy significantly improved rhinoconjunctivitis‐related QOL during the grass pollen season.